2014
DOI: 10.1371/journal.pone.0109461
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Engineered Lactococcus lactis Protect against House Dust Mite Allergy in a BALB/c Mouse Model

Abstract: BackgroundMucosal vaccine based on lactic acid bacteria is an attractive concept for the prevention and treatment of allergic diseases, but their mechanisms of action in vivo are poorly understood. Therefore, we sought to investigate how recombinant major dust mite allergen Der p2-expressing Lactococcus lactis as a mucosal vaccine induced the immune tolerance against house dust mite allergy in a mouse model.MethodsThree strains of recombinant L. lactis producing Der p2 in different cell components (extracellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 48 publications
0
15
1
Order By: Relevance
“…L. plantarum was cultured in MRS broth, and L. lactis was cultured in GM17 medium as described. 58 Individual GF mice were gavaged with 100 ÎźL (1 × 10 7 CFU) of each strain, feces were collected after inoculation and subjected to morphological examination under a microscope. Bacterial DNA was extracted from collected feces, and primers (listed in Supplementary Information, Table S1) specific for L. lactis and L. plantarum were used for PCR identification.…”
Section: Mono-colonization With Lactobacillus Plantarum or Lactococcumentioning
confidence: 99%
“…L. plantarum was cultured in MRS broth, and L. lactis was cultured in GM17 medium as described. 58 Individual GF mice were gavaged with 100 ÎźL (1 × 10 7 CFU) of each strain, feces were collected after inoculation and subjected to morphological examination under a microscope. Bacterial DNA was extracted from collected feces, and primers (listed in Supplementary Information, Table S1) specific for L. lactis and L. plantarum were used for PCR identification.…”
Section: Mono-colonization With Lactobacillus Plantarum or Lactococcumentioning
confidence: 99%
“…With respect to inhaled allergens, the modulation of allergic immune responses to the major dust mite allergen Der p2 by recombinant L. lactis has recently been described ( 103 ).…”
Section: Lactis For the Generation And Maintenance Of Antmentioning
confidence: 99%
“…Some studies have combined the bacterial effect with an expressed antigen either for food hypersensitivity or aero-allergens. The administration of L. lactis displaying the recombinant allergen intracellularly, in the extracellular space or cell wall-anchored show its capacity to modulate the Th2-based specific antibody responses, in the case of the allergen Ara h 2 against peanut allergic [ 93 ] and the Der p2 allergen against the dust mite allergy [ 94 ]. In the second study, the authors also observed a diminution in the cellular infiltration and inflammatory response.…”
Section: Reviewmentioning
confidence: 99%